Nonlinear analysis of the progressive collapse of reinforced concrete plane frames using a multilayered beam formulation - C. E. M. Oliveira; E. A. P. Batelo; P. Z. Berke; R. A. M. Silveira; T. J. Massart (Revista IBRACON de Estruturas e Materiais)
This work investigates the response of two reinforced concrete (RC) plane frames after the loss of a column and their potential resistance for progressive collapse. Nonlinear dynamic analysis is performed using a multilayered Euler/Bernoulli beam element, including elasto-viscoplastic effects. The material nonlinearity is represented using one-dimensional constitutive laws in the material layers, while geometrical nonlinearities are incorporated within a corotational beam formulation. The frames were designed in accordance with the minimum requirements proposed by the reinforced concrete design/building codes of Europe (fib [1-2], Eurocode 2 [3]) and Brazil (NBR 6118 [4]). The load combinations considered for PC analysis follow the prescriptions of DoD [5]. The work verifies if the minimum requirements of the considered codes are sufficient for enforcing structural safety and robustness, and also points out the major differences in terms of progressive collapse potential of the corresponding designed structures.